The Impact of Strategic Sensitivity on Organizational Immunity: An Analytical Research in the Iraqi Ministry of Education - Amin, Muhammad Abdullah; Ali Mhaibes, Hossam (Journal of Economics and Administrative Sciences, 2024)
The current business environment is characterized by a set of complex and rapid changes, which requires organizations to respond and adapt to these changes to sustain their performance. By relying on a set of new methods and means that enable it to anticipate problems and sudden changes and develop the necessary solutions to them. This comes through the strategic sensitivity possessed by organizational leaders, which enables them to anticipate the future and seize available opportunities, which contributes to providing distinguished services or products and preserving the organization’s survival and continuity. The current research aims to determine the impact of strategic sensitivity in enhancing organizational immunity in the Iraqi Ministry of Education, as the strategic sensitivity variable included two dimensions (strategic foresight and strategic insight), and the organizational immunity variable included three dimensions (organizational learning, organizational memory, and organizational DNA). Selecting a purposive sample of 349employees who include all leadership levels in the ministry and consist of division official, department director, assistant general manager, general manager, undersecretary, and advisor. The research used the descriptive analytical method and the questionnaire as the main tool for collecting data, as the number of questionnaires suitable for the analysis reached 330. In addition, a set of statistical methods were used in the analysis, such as the simple correlation coefficient (Pearson), and descriptive analysis methods using (SPSS, AMOS.v25). A set of results was reached, the most important of which is the clear and significant impact of strategic sensitivity in building and strengthening the immunity of the relevant ministry, meaning that there is a significant impact of strategic sensitivity on organizational immunity. Paper type: Research paper.